2011
DOI: 10.1007/s00213-011-2316-2
|View full text |Cite
|
Sign up to set email alerts
|

One-trial behavioral sensitization in preweanling rats: differential effects of cocaine, methamphetamine, methylphenidate, and d-amphetamine

Abstract: Rationale Preweanling rats exhibit robust one-trial cocaine-induced behavioral sensitization; however, it is uncertain whether other psychostimulants can also induce sensitization in young rats using the one-trial procedure. Objective The purpose of this study was to determine whether methamphetamine, methylphenidate, and D-amphetamine are capable of inducing one-trial locomotor sensitization in preweanling rats. Methods In a series of four experiments, rats were pretreated with cocaine (30 mg/kg), methamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…; Sobrian et al , 2003), while other ontogenetic effects are a consequence of programmed changes in the rats’ behavioral repertoire (Moody and Spear, 1992). In terms of this study, it was previously reported that methamphetamine does not induce one-trial behavioral sensitization during the late preweanling period (i.e., PD 19–21), whereas cocaine causes robust context-independent behavioral sensitization at the same age (McDougall et al, 2011a). Whether these two sets of findings are unique to the late preweanling period is unknown.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…; Sobrian et al , 2003), while other ontogenetic effects are a consequence of programmed changes in the rats’ behavioral repertoire (Moody and Spear, 1992). In terms of this study, it was previously reported that methamphetamine does not induce one-trial behavioral sensitization during the late preweanling period (i.e., PD 19–21), whereas cocaine causes robust context-independent behavioral sensitization at the same age (McDougall et al, 2011a). Whether these two sets of findings are unique to the late preweanling period is unknown.…”
Section: Introductionmentioning
confidence: 81%
“…It was originally reported that methamphetamine would not support one-trial behavioral sensitization during the late preweanling period (i.e., on PD 21) (McDougall et al , 2011a). The present study greatly extends these findings by showing that rats will exhibit robust one-trial context-independent behavioral sensitization when methamphetamine is administered to younger age groups (PD 12–13 or PD 16–17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies, we previously reported that young rats show strong one-trial behavioral sensitization, but the age at which sensitized responding was exhibited depended on the psychostimulant being administered (McDougall et al 2011a, 2013; Kozanian et al 2012). For example, amphetamine and METH caused the most robust sensitized responding at PD 13 and PD 17, while cocaine only produced behavioral sensitization in older animals (i.e., at PD 21).…”
Section: Discussionmentioning
confidence: 99%
“…NPA has not been tested using this methodology, so a multi-dose parametric experiment was conducted to determine the early ontogeny of one-trial NPA-induced behavioral sensitization. The doses of cocaine and METH used in the present study were chosen because of their ability to produce strong one-trial behavioral sensitization in preweanling rats (McDougall et al 2007, 2011a; Herbert et al 2010). In all cases, lower doses of DA agonists were administered on the test day, relative to the pretreatment day, in order to preferentially induce locomotor activity rather than stereotypy (for a fuller discussion, see Robinson and Becker 1986).…”
Section: Introductionmentioning
confidence: 99%